The spectrum of CYP21A2 gene mutations in patients with classic salt wasting form of 2l‐hydroxylase deficiency in a Chinese cohort. Issue 11 (21st September 2020) - Liu, Yang; Zheng, Jie; Liu, Nan; Xu, Xiaowei; Zhang, Xinjie; Zhang, Ying; Li, Guoxu; Liu, Geli; Cai, Chunquan; Shu, Jianbo
Abstract: Background: 21‐Hydroxylase deficiency (21‐OHD) caused by the CYP21A2 gene mutations is the most common form of congenital adrenal hyperplasia. It is an autosomal recessive disorder that results in defective synthesis of cortisol and aldosterone. The incidences of various CYP21A2 gene mutations and the genotype–phenotype correlations vary among different populations. Materials and Methods: The clinical and molecular data of 22 patients were analyzed in this study. All patients were recruited from the neonatal intensive care unit. Locus‐specific polymerase chain reaction and Sanger sequencing were applied to identify gene micro‐conversions, and multiplex ligation‐dependent probe amplification was used to detect large fragment deletions/conversions. Then, the genotypes were categorized in to Null, A, B, C, and D groups to analyze the relationships between genotypes and phenotypes. Results: All 22 patients were classified into classic salt wasting form of 21‐OHD. Molecular defects were detected in 44 alleles (100%). Micro‐conversion mutation IVS2‐13A/C>G (70.5%) is most common in our cohort, followed by large gene deletions and conversions (22.7%). The other mutations present were p.R357 W (4.5%) and E6 Cluster (2.3%). Genotypes of 22 patients (100%) were consistent with the predictive phenotypes. Conclusion: In this study, we identified the mutation spectrum of CYP21A2 gene in Chinese patients, especially the younger age cohort in pediatrics. Micro‐conversions were the most popular mutations. Moreover, the genotypes and phenotypes were well correlated in this cohort of salt wasting 21‐OHD recruited from neonatal intensive care unit. Abstract : We identified the mutation spectrum of CYP21A2 gene in Chinese patients, especially the younger age cohort admitted in NICU. The genotypes and phenotypes in 21‐OHD were well correlated.